Notes on the history of the Nicaraguan Caribbean Coast / Ronald Brooks - Brooks, Ronald (Nicaragua : URACCAN 2000)
Our ethnic groups, we must try to understand our history, our communities, the communities at the mouth of Rio Grande, the melting pot, our indigenous pioples, afro-caribbeabs on the coast, nourishing the dream, miskitus and their organization, the reincorporation of mosquito reservation, the moravians on the Atlantic Coast.
Illustrated cover, contents, map, illustrations, tables
Keywords: 1. NICARAGUAN 2. HISTORY-NICARAGUAN-CARIBBEAN-COAST 3. ETHNIC GROUPS-URACCAN 4. HISTORY